A Robust strategy enabling addressable porous 3D carbon-based functional nanomaterials in miniaturized systems. Issue 8 (11th February 2019) - Wongkaew, Nongnoot; Simsek, Marcel; Arumugam, Palaniappan; Behrent, Arne; Berchmans, Sheela; Baeumner, Antje J.
Abstract : Facile construction of high performance carbon nanofiber electrodes via electrospinning and one-step laser-induced carbonization for electrochemical sensors in miniaturized systems. Abstract : 3D-porous carbon nanomaterials and their hybrids are ideal materials for energy storage and conversion, biomedical research, and wearable sensors, yet today's fabrication methods are too complicated and inefficient to implement into miniaturized systems. Instead, it is shown here that 3D-carbon nanofibrous electrodes of various designs, shapes and sizes, on flexible substrates, under ambient conditions and without complicated equipment and procedures can simply be "written" via a one-step laser-induced carbonization on electrospun nanofibers. Analytical functionalities are realized as full control over native polymer chemistry doping of the polymer ( e.g. with metals) is provided. Similarly, being able to control mat morphology and its impact on the electroanalytical performance was studied. Ultimately, optimized writing conditions were harnessed for superior (bio)analytical sensing of important biomarkers (NADH, dopamine). The new procedure hence paves the way for future controlled studies on this 3D nanomaterial, for a multitude of functionalization and design possibilities, and for mass production capabilities necessary for their application in the real world.